2011
DOI: 10.1177/0022022110381121
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cognitive Appraisals of Communication Competence in Conflict Interactions: A Study Involving Western and Chinese Cultures

Abstract: This study investigated differences between people from Western and Chinese cultures on perceived competence (effectiveness and appropriateness) of the other party's communication during conflict. First, a pilot study with 30 employees in Singapore examined appraisals of communication competence in recalled intercultural conflict incidents. Western expatriates judged competence of the other party mainly on whether the communication style was direct and engaged, deemed to be judgments of effectiveness. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In addition, in highly interdependent and hierarchical societies, such as China, maintaining interpersonal harmony is of great importance during social interactions (Leung, 1987; Markus & Kitayama, 1991). Collectivists are expected to avoid hurting feelings, to minimize outward expression of conflict, and to perform norm appropriate behaviors to meet the face-support constraint (Brew, Tan, Booth, & Malik, 2011; Morris & Peng, 1994). Therefore, it is possible that Chinese targets who feel angry about the instigator of incivility would replace the direct interpersonal inappropriateness (i.e., reducing OCB toward other individuals) with less overt responses (i.e., reducing OCB toward organization or increasing CWB) to retaliate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in highly interdependent and hierarchical societies, such as China, maintaining interpersonal harmony is of great importance during social interactions (Leung, 1987; Markus & Kitayama, 1991). Collectivists are expected to avoid hurting feelings, to minimize outward expression of conflict, and to perform norm appropriate behaviors to meet the face-support constraint (Brew, Tan, Booth, & Malik, 2011; Morris & Peng, 1994). Therefore, it is possible that Chinese targets who feel angry about the instigator of incivility would replace the direct interpersonal inappropriateness (i.e., reducing OCB toward other individuals) with less overt responses (i.e., reducing OCB toward organization or increasing CWB) to retaliate.…”
Section: Discussionmentioning
confidence: 99%
“…Students' discussion behaviors in student-centered education across cultures 4 interdependence of group members, and behaviors that are shaped by group norms and values (Hui and Triandis 1986).It should be noted though that cultural diversity within Eastern and Western regions can be larger than across, and they cannot be characterized straightforwardly as either collectivistic or individualistic. Previous research has, however, shown a general preference of Eastern cultures for collectivistic communication styles, which tend to favor harmonious group relations, avoidance of conflict, and indirect communication as opposed to a more confrontational, direct, and outspoken style of individualistic cultures (Brew et al 2011;Oetzel et al 2001;Smith 2011). Consequently, it seems logical to assume that the distinction between individualistic Western cultures and collectivistic Eastern cultures is likely to lead to cross-cultural differences in communicative behaviors demonstrated by students in discussions in student-centered education.…”
Section: Introductionmentioning
confidence: 88%
“…Cross-cultural differences in communication styles have been extensively researched, particularly in Eastern and Western cultures (e.g. Brew et al 2011;Smith 2011;Yeung and Kashima 2012). Eastern cultures are often characterized as collectivistic, in contrast to Western cultures, which are regarded as individualistic (Hofstede 2001;Triandis 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research on behavioral competencies typically centers on two dimensions: effectiveness in implementing communicative skills to accomplish goals and the appropriateness in using them to adhere to the norms and rules of particular situations (Canary and Spitzberg 1987;Spitzberg and Cupach 1989). Scholars have linked both effectiveness and appropriateness to communication competencies in conflict management styles, interpersonal conflicts, and intercultural conflict interactions, but not to negotiation per se (Brew et al 2011;Canary and Spitzberg 1989). In this way, competence is the intersection of abilities perceived to be effective and appropriate.…”
Section: The Social Psychological Perspectivementioning
confidence: 99%